Keragaan Pertumbuhan dan Biomassa Varietas Kedelai (Glycine max (L)) di Lahan Sawah dengan Aplikasi Pupuk Organik Cair - Eka Widiastuti; Evy Latifah (Jurnal Ilmu Pertanian Indonesia, 2016)
Liquid organic fertilizers (POC) is an alternative to the addition of macro and micro nutrients to improve the productivity of soybean. The aim of the research was to determine the effect of varieties and POC Biotek concentration and the interaction on growth and yield of soybean. The experiment was conducted in BPTP East Java experiment field, Malang Karangploso from February-May 2012. Randomized Complete Block Design (RCBD) factorial with three replication was used in this experiment. The first factor is five soybean varieties and the second factor is four POC Biotek concentration. The result of experiment show that varieties significantly different with POC concentration and had interaction varieties and Biotek POC concentration. Burangrang varieties with the Biotek POC concentration 4 ml/l give higher yield (seed weight 17.67 g). Burangrang varieties can be used as a potential alternative to animal feed because it was high dry weight (0.70 kg).